Current Developments In Lte/Lte-Advanced : Adaptive-Proportional Fair Scheduling In Lte - Ismail, Mohd Khairy; Awang Md Isa, Azmi; Johal, Mohammad Syahrir; Mohd Zin, Mohd Shahril Izuan (Penerbit Universiti, UTeM, 2015)
This paper provides analytical expressions to validate and evaluate the performance of Long Term Evolution (LTE) network in terms of throughput, spectral efficiency and SINR which are subjected to the constraint of proportional fairness amongst users from the EnodeB. The proportional fair scheduling (PFS) algorithm is mainly focused on bandwidth allocation criterion in LTE networks for supporting high resource utilization while maintaining high fairness among network flows to each distributed User Equipment (UE). The most challenge of a PFS problem is the lack of analytic expression. Though the PFS algorithm has been a research focus for some time, the results are mainly obtained from computer simulations. The current existing research applies a simplified form of the PFS preference metric and the given analytic expression is capable to support certain cases. The proposed model is refined with respect to uniform modulation and coding, as applied in LTE networks. Besides, we show that our models are approximate estimates for the performance of rate-based proportional fair scheduling, while they outperform some simpler prediction models from related work significantly.